The Co-Organization of Demonstratives and Pointing Gestures. Issue 8 (16th November 2016) - Cooperrider, Kensy
Abstract : Demonstratives and pointing gestures are universal, early emerging, and ubiquitous, and it has long been claimed that there is a special relationship between them. But what exactly is the nature of this relationship? The present study investigates this question using a referential communication task. Speakers referred to targets that were near or far and pointed with the hand (more ambiguous) or a laser pointer (less ambiguous). Demonstratives and pointing frequently co-occurred but were also related in less obvious ways: speakers (1) used fewer demonstrative-pointing combinations when pointing was ambiguous, (2) preferred proximal demonstratives when pointing and distals when not pointing, and (3) used fewer proximal demonstratives when pointing was ambiguous. These findings suggest that the relationship between demonstratives and pointing goes beyond one of mere co-occurrence or functional resemblance and reveal some of the principles by which speakers organize these two powerful tools in relation to each other.